2004
DOI: 10.1002/ejoc.200400493
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of 3‐(trans‐2‐Nitrocyclopropyl)alanine, a Constituent of the Signal Metabolite Hormaomycin

Abstract: Feeding experiments with Streptomyces griseoflavus using deuterium-labeled racemic 3,3-[ and 6,6-[D 2 ]-lysine (6e), and 3-amino-5-(2-amino-1,1-dideuterioethyl)-4,5-dihydrofuran-2-one dihydrochloride (34·2HCl) were carried out in order to obtain detailed information about the hitherto unknown biosynthetic pathway from lysine to the unusual amino acid 3-(trans-2Ј-nitrocyclopropyl)alanine [(3-Ncp)Ala] (2), which is a building block of hormaomycin 1a. The corresponding lysine dihydrochlorides were prepared in 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
0
24
0
1
Order By: Relevance
“…Stable isotope feeding experiments have revealed that 133 is derived from L-lysine (Scheme 28B). 365 Loss of deuterium from the C 4 position of this amino acid suggests that oxidation and intramolecular cyclization events take place during the biosynthesis of 133 . In one proposed mechanism, an initial four-electron oxidation of the N6-amine of L-lysine affords the oxime intermediate 134 which is followed by concerted cyclopropanation and lactone-ring opening to generate the nitrosocyclopropane 135 .…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…Stable isotope feeding experiments have revealed that 133 is derived from L-lysine (Scheme 28B). 365 Loss of deuterium from the C 4 position of this amino acid suggests that oxidation and intramolecular cyclization events take place during the biosynthesis of 133 . In one proposed mechanism, an initial four-electron oxidation of the N6-amine of L-lysine affords the oxime intermediate 134 which is followed by concerted cyclopropanation and lactone-ring opening to generate the nitrosocyclopropane 135 .…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…[6] Important examples of natural nonaromatic nitro compounds are nitropropionic acid [7] and the bacterial signal metabolite hormaomycin. [8,9] Surprisingly, the biosynthesis of aromatic nitro groups is understood only to a small extent. One possible pathway involves aromatic substitution of nitro groups, as is the case for the unusual nitro alkaloid 1-nitroaknadinine (7) from Stephania sutchuenensis, which occurs simultaneously with the non-nitrated alkaloid.…”
mentioning
confidence: 99%
“…[1e, 13,14] Preparation of Cyclopropylalanine Derivatives 1,1-Dideuterio-(trans-2Ј-nitrocyclopropyl)methanol (9): To a stirred solution of the ester 8 (9.36 g, 50.0 mmol) in anhydrous diethyl ether (150 mL) was added LiAlD 4 (25.0 mmol, 30.1 mL of a 0.83 n solution in THF) under Ar at ambient temp. over a period of 1 h. Then the reaction mixture was stirred at the same temp.…”
Section: Methodsmentioning
confidence: 99%
“…Upon feeding the deuterium-labeled amino acid rac-[D 2 ]-3·HCl, the labeled hormaomycin 1b was obtained, as indicated by a ca. 90 % decrease of the intensities of the 3-H proton signals of both (3-Ncp)Ala fragments of hormaomycin in the 1 H-NMR spectrum as well as a significant decrease and broadening of the corresponding C-3 signals in its 13 C-NMR spectrum. Thus, 3-(trans-2Ј-nitrocyclopropyl)alanine is accepted by the hormaomycin synthetase and therefore should be established prior to the assembly of the peptide lactone.…”
Section: Feeding Experimentsmentioning
confidence: 96%
See 1 more Smart Citation